2014
DOI: 10.1021/jp506711f
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Transient Absorption Spectroscopy Study of the Early Events of Norfloxacin in Aqueous Solutions with Varying pH Values

Abstract: The photophysics and photochemistry of norfloxacin (NF) have been investigated in aqueous solutions of different pH using femtosecond transient absorption spectroscopy (fs-TA). Resonance Raman spectroscopic experiments on NF have also been conducted in aqueous solutions of different pH to characterize the vibrational and structural information on the initial forms of NF. The experimental results in combination with density functional theory calculations of the key intermediates help us to elucidate the early e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
(90 reference statements)
2
10
0
Order By: Relevance
“…This bonding motif can be disturbed/weakened by competing intermolecular hydrogen‐bonding, e.g., by water, thus leading to a strong quenching effect as observed in the present study. In future studies, ultrafast time‐resolved spectroscopy may be used to evaluate the hydrogen‐mediated interaction dynamics, and thus elucidate the quenching pathway of these interesting fluorophores by hydrogen‐bond donors . Regardless, our results have shown that the emission of N ‐amidinated ciprofloxacin derivatives is strongly responsive to hydrogen‐bond donors in nonpolar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…This bonding motif can be disturbed/weakened by competing intermolecular hydrogen‐bonding, e.g., by water, thus leading to a strong quenching effect as observed in the present study. In future studies, ultrafast time‐resolved spectroscopy may be used to evaluate the hydrogen‐mediated interaction dynamics, and thus elucidate the quenching pathway of these interesting fluorophores by hydrogen‐bond donors . Regardless, our results have shown that the emission of N ‐amidinated ciprofloxacin derivatives is strongly responsive to hydrogen‐bond donors in nonpolar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…The spectral properties of NOF are highly sensitive to the environment due to the pH-dependent prototropic equilibrium (Figure a). Representative examples of pH-dependence of the spectral properties of the drug are illustrated in Figure b. The absorption profile of NOF at neutral pH (pH 7.40) exhibits a strong absorption at λ abs ≈ 270 nm attributable to the aromatic nucleus and a long wavelength absorption in the region 300–350 nm with two subpeaks (λ abs of ∼325 and 335 nm) emanating from n → π* electronic transition. Decrease in medium pH from neutral (pH 7.40) to acidic (pH 4.0) regime is found to accompany (Figure b inset) a discernible red-shift of the short wavelength absorption by ∼5 nm (from λ abs of ∼270 to ∼275 nm), with concomitant appearance of a tail at the long wavelength region (beyond 350 nm).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The spectral properties of NOF are highly sensitive to the environment due to the pH-dependent prototropic equilibrium (Figure a). Representative examples of pH-dependence of the spectral properties of the drug are illustrated in Figure b. The absorption profile of NOF at neutral pH (pH 7.40) exhibits a strong absorption at λ abs ≈ 270 nm attributable to the aromatic nucleus and a long wavelength absorption in the region 300–350 nm with two subpeaks (λ abs of ∼325 and 335 nm) emanating from n → π* electronic transition. Decrease in medium pH from neutral (pH 7.40) to acidic (pH 4.0) regime is found to accompany (Figure b inset) a discernible red-shift of the short wavelength absorption by ∼5 nm (from λ abs of ∼270 to ∼275 nm), with concomitant appearance of a tail at the long wavelength region (beyond 350 nm). This conforms to the signature of prototropic transformation of NOF from zwitterionic (in neutral pH) to cationic (in acidic pH) form, which complies well with reported literature suggesting that the prototropic equilibrium of NOF in the pH range 2.5–7.5 is restricted within the zwitterionic and cationic species only. Concurrently, the remarkable sensitivity of the emission spectral properties of NOF on medium pH is also displayed in Figure b.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pK a values are approximately 6.2 and 8.5 [23,24]. Therefore, it indicated that the structure of its aqueous solution is displayed in four forms, namely, neutral form, tautomeric form, anionic form and cationic form [25]. We suspect that the neutral form of NOR has better chance to adsorb on the surface of Ag 7 Au 3 [26].…”
Section: Optimization Of Ph In Nor Solutionmentioning
confidence: 93%